Media-Directed Parent Training. Symposium Parent Training: Models and Evaluation of Outcome - Kashima, Kathleen ([Washington, D.C.] : Distributed by ERIC Clearinghouse, 1986)
In a search for effect dissemination methods for parent training programs, a videocassette program was developed as an alternative to traditional, professionally led programs to train parents in teaching self-help skills to their developmentally disabled children. Effectiveness of the videocassette approach was tested when 55 families in Los Angeles County with a moderately to severely developmentally disabled child (mean age 5.9) were randomly assigned to one of three conditions: (1) live training by a professional who used a variety of methods such as lectures, group exercises, and brief videotaped vignettes; (2) video training facilitated by agency staff who had no prior experience with the curriculum content; and (3) a delayed training control group. In both training approaches, four sessions covered the following topics: (1) identifying a self-help skill to teach; (2) teaching techniques (e.g., task analysis, backward chaining); (3) using rewards; and (4) troubleshooting problems. Compared to parents in the traditional leader-directed group, parents in the video program had equal attendance, participation, and understanding; demonstrated equal mastery of behavioral principles on the 20-item Behavioral Vignettes Test; and gave equally high evaluations of the program. (JW)
ERIC Note: Paper presented at the Annual Meeting of the American Association on Mental Deficiency (110th, Denver, CO, May 25-29, 1986).
May also be available online. Address as at 14/8/18
Microfiche.
Keywords: Audiovisual Aids; Behavior Modification; Elementary Education; Instructional Materials; Moderate Mental Retardation; Parent Education; Parent Materials; Parent Student Relationship; Preschool Education; Self Care Skills; Severe Mental Retardation; Teaching Methods; Videotape Cassettes; Behavioral Vignettes Test; Reports, Research; Speeches/Meeting Papers